Innovative Leadership in the Revitalization of Pasar Pagi Samarinda Through the Digitalization of Trader Governance - Afni Nurvita Damayanti Wijaya; Muhammad Hasbi Mo’a W.A; Iman Surya (Jurnal Kajian dan Penelitian Umum, 2026)
This study aims to analyze innovative leadership in the revitalization of Pasar Pagi Samarinda as an effort to reform the governance of traditional markets. This research employed a qualitative approach with a case study design, using document analysis of regulations, statistical data, official government news, and academic literature. The findings indicate that the revitalization of Pasar Pagi is not merely concerned with physical development, but also with governance transformation through the digitalization of trader data, validation of stall ownership, and the strengthening of transparency in market management. Innovative leadership is reflected in the capacity of the local government to integrate building-risk mitigation, service modernization, and the protection of traders’ business sustainability. However, the revitalization process still requires strong collaboration among the government, DPRD, market managers, and traders to ensure that relocation and post-revitalization management are carried out in a fair and participatory manner. This study emphasizes that the success of traditional market revitalization should be measured by the sustainability of governance, rather than solely by the completion of infrastructure. The novelty of this study lies in mapping the relationship between a vision for change, digitalization, stakeholder collaboration, and the sustainable governance of local traditional markets.